THE CHEMICAL COMPOSITION PECULIARITIES OF G, K GIANTS - Mishenina, T. V. (Одеські астрономічні публікації, 2017)
The review of the observed chemical composition in different groups of G, K - giants with peculiarities in spectra is presented. The old and young disk giants, Ba- and CH- stars, CN-Week and CN-strong giants, R stars, Li-strong giants, SMR stars have been discussed.